Novel mutations identified in Chinese families with autosomal dominant congenital cataracts by targeted next-generation sequencing - Shan Li; Jianfei Zhang; Yixuan Cao; Yi You; Xiuli Zhao (BMC, 2019)
Abstract Background Congenital cataract is a clinically and genetically heterogeneous visual impairment. The aim of this study was to identify causative mutations in five unrelated Chinese families diagnosed with congenital cataracts. Methods Detailed family history and clinical data were collected, and ophthalmological examinations were performed using slit-lamp photography. Genomic DNA was extracted from peripheral blood of all available members. Thirty-eight genes associated with cataract were captured and sequenced in 5 typical nonsyndromic congenital cataract probands by targeted next-generation sequencing (NGS), and the results were confirmed by Sanger sequencing. Bioinformatics analysis was performed to predict the functional effect of mutant genes. Results Results from the DNA sequencing revealed five potential causative mutations: c.154 T > C(p.F52 L) in GJA8 of Family 1, c.1152_1153insG(p.S385Efs*83) in GJA3 of Family 2, c.1804 G > C(p.G602R) in BFSP1 of Family 3, c.1532C > T(p.T511 M) in EPHA2 of Family 4 and c.356G > A(p.R119H) in HSF4 of Family 5. These mutations co-segregated with all affected individuals in the families and were not found in unaffected family members nor in 50 controls. Bioinformatics analysis from several prediction tools supported the possible pathogenicity of these mutations. Conclusions In this study, we identified five novel mutations (c.154 T > C in GJA8, c.1152_1153insG in GJA3, c.1804G > C in BFSP1, c.1532C > T in EPHA2, c.356G > A in HSF4) in five Chinese families with hereditary cataracts, respectively. NGS can be used as an effective tool for molecular diagnosis of genetically heterogeneous disorders such as congenital cataract, and the results can provide more effective clinical diagnosis and genetic counseling for the five families.